Hubungan Body Image dan Pengetahuan Gizi dengan Konsumsi Fattening Foods pada Siswa SMA di Surakarta - Ismi Arifatul Khoridah; Dyah Intan Puspitasari; Firmansyah Firmansyah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Adolescence is a vulnerable period in the formation of eating behaviors, where body image and nutritional knowledge can affect the tendency to consume fattening foods. This study aims to determine the relationship between body image and nutritional knowledge with the consumption of fattening foods in high school students in the city of Surakarta. This study used an observational quantitative design with a cross-sectional approach on 174 respondents who were selected using multistage random sampling and proportional random sampling techniques. Data were collected using body image questionnaires (MBSRQ-AS), nutrition knowledge questionnaires, and SQ-FFQ, then analyzed using the Spearman Rank test. The results showed that most of the respondents had a negative body image (51.72%), good nutrition knowledge (84.49%), and consumption of fattening foods in the category of excess intake (63.8%). There was no relationship between body image and fattening food consumption (p=0.126), but there was a relationship between nutritional knowledge and fattening food consumption (p=0.034; r=-0.161), which shows that the better the nutritional knowledge, the lower the consumption of fattening foods. Thus, improving nutrition education is important to support the formation of healthier consumption behaviors in adolescents.